Correlation of ray tracingtechnique and ITDG to predict speech inetlligibility [electronic resource] - 242149 Mun, Hou Kit; Mokhtar Harun (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Kejuruteraan (Elektrik - Elektronik dan Telekomunikasi)) - Universiti Teknologi Malaysia, 2007